Always unfinished business : of singing the country - Somerville, Margaret; Bates, Badger; De Carteret, Phoenix; Hamm, Treahna, 1965-; Marshall, Chrissiejoy; Martin, Sarah; Wallace Daphne, 1964-; Switchback Gallery (Vic.) ([Churchill, Vic.] : Margaret Somerville, 2008)
"Featuring the work of: Yorta Yorta artist, Treahna Hamm; Paakantji artist, Badger Bates, with:Gamaroi/Ullaroi artist, Daphne Wallace; U'Allayi researcher, Chrissiejoy Marshall". -- verso of title page.
"To accompany the exhibition 'Bubbles on the Surface III', Switchback Gallery, 12 December 2008 to 12 March 2009". -- verso of title page.
"Editors: Margaret Somerville, Phoenix de Carteret". -- verso of title page
Keywords: Hamm, Treahna, -- 1965- -- Exhibitions; Bates, Badger -- Exhibitions; Wallace, Daphne -- 1964- -- Exhibitions; Bubbles on the Surface III; Switchback Gallery (Vic.) -- Exhibitions; Art, Aboriginal Australian -- Victoria -- Exhibitions; Artists, Aboriginal Australian -- Exhibitions